Perbandingan Sosial dan Iri Hati (Envy) Pada Mahasiswa: Analisi Blibiometrik - Abdillah, Aufa; Lestari , Sri; Anganti , Nisa Rahmah Nur; Taufik, Taufik (Jurnal Ners, 2025)
Envy is a complex social emotion that frequently arises in interpersonal interactions, particularly through social comparison. Among college students, this emotion is further intensified by competitive academic environments and the influence of social media, which often serve as benchmarks for success and achievement. When not properly managed, envy can negatively impact students’ mental health, especially in today’s digital era. This study aims to examine the trends and research patterns related to envy among college students through a bibliometric analysis approach. The analysis was conducted using VOSviewer software on 255 scientific articles indexed in the Scopus database from 1963 to 2025. Articles were selected based on three criteria: written in English, published in article format, and containing the keyword "envy". The results revealed a significant increase in publication numbers in 2021 and 2022, while the lowest publication rates occurred during the 2000–2010 period. Of the 680 identified authors, only 105 collaborated with one another, forming seven researcher clusters, indicating a low level of scholarly collaboration in this field. One promising research direction is the investigation of mechanisms for transforming malicious envy into benign envy, which holds relevance for psychological interventions and character education among students.